The Vampire of Capital and its Death Drive: Validity of Marx and Freud in the Face of the Current Structural Violence of Capitalism - Pavón-Cuellar, David (2023)
The current structural violence of capitalism is reflexively addressed through notions provided by Marx and Freud. The Freudian notion of the death drive allows us to reinterpret the Marxian metaphor of the vampire of capital that absorbs the living to transmute it into more and more dead money. This reinterpretation reveals unsuspected aspects in violent manifestations of the capitalist system.